Дослідження історії та пам'яток Волинського воєводства науковими товариствами Другої Речі Посполитої у 1921-1939 рр. - Кінд-Войтюк, Наталія; Kind-Voitiuk, Nataliia (Східноєвропейський національний університет імені Лесі Українки, 2014)
Висвітлюється діяльність Волинського товариства краєзнавців і охорони пам’яток старовини та Волинського товариства друзів наук щодо виявлення, вивчення і збереження історико-культурних пам’яток Волині у міжвоєнний період.

In the article the activity of Volyn Regional Studies associations and Volyn association of the friends of the science is depicting for desplay, investigation, reservation of historical and cultural monuments of Volyn region in the period between the wars. On the basis of archival materials are characterized by areas of research communities: scientific support to researchers, the collection of materials for the Polish museums, publishing, scientific konferentsіy inventory of archival materialov. Particular attention is paid to the organization of tourism activities, conducting local history tours, training guides.
The Scientific-Social Associations of the Poland in Research of the History and Monuments of Volyn Region
Keywords: наукові товариства; історична пам'ятка; археологія; історико-краєзнавчі дослідження; видавнича діяльність; scientific associations; historical monument; archaeology; historical and regional research; publishing work